An investigation into the relationship between the leadership competencies, emotional intelligence and leadership styles of Russian managers working for MNCs - Genderen,Eric Van (2010)
The need for greater understanding of international leadership models has escalated in tandem with the globalization of trade and commerce. This comparative-cultural research highlights a deficit of up-to-date comparative data on Russian organizational leadership, whilst articulating the demand for Russia-appropriate leadership development expertise. Contributions of this research to theory include: the identification of an up-to-date leadership profile of Russian managers, in competency terms, which can be compared with other cultures; a comparative cultural assessment of Russian managers based on Emotional Intelligence; a comparison of Russian managers at different levels of large companies, with special attention to their similarities and differences. Implications of this research for practitioners include: the ability for organizations operating in Russia to identify/develop leaders based on their personal leadership profiles (executive training and development), as assessed by the Leadership Dimensions Questionnaire; the potential for identifying and fostering competencies required of managers at higher levels within the organization (promotion; as roles and responsibilities differ at various levels within an organization).